PENERAPAN METODE DIRECT INSTRUCTION DALAM MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA DI SMK - Herawati Arief S; Supriadi Supriadi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The aims of this study to determine the ability to write poetry through the direct instruction method in SMK students. The approach used in this study uses a qualitative approach using classroom action research methods. This research was conducted at SMKS Yapmi Makassar with a total population of 125 people. With a total sample of 36 students consisting of 4 boys and 32 girls. Sampling was carried out by means of clustering simple random sampling, namely a random draw. This research was conducted in two cycles, namely cycle I and cycle II. Each cycle is carried out in accordance with the changes to be achieved between cycle I and cycle II which are interrelated components. Data collection through the format of observation and ability to write poetry, then analyzed qualitatively and quantitatively. The results showed that learning using the direct instruction method could improve students' ability to write poetry at SMK Makassar. This is indicated by an increase in the average score of the ability to write poetry based on the building blocks of poetry consisting of diction, imagination, typography and message from cycle I, namely 52.50, then it increased very significantly in cycle II, namely to 83.61. While the achievement of learning completeness in the first cycle was 8.3% and increased in the second cycle, which was 100%.